“We are the ones who will have to make the change”: Cuban health cooperation and the integration of Cuban medical graduates into practice in the Pacific - Sharon McLennan; Cristine Werle (Human Resources for Health, 2023)
Abstract Background This paper responds to Asante et al. (in Hum Resour Health, 2014), providing an updated picture of the impacts of Cuban medical training in the Pacific region based on research carried out in 2019–2021, which focused on the experiences of Pacific Island doctors trained in Cuba and their integration into practice in their home countries. Methods The research focussed on two case studies—Solomon Islands and Kiribati. Study methods for this research included multi-sited ethnographic methods and semi-structured interviews as well as qualitative analysis of policy documents, reports, and media sources. Results The Cuban health assistance programme has had a significant impact on the medical workforce in the Pacific region increasing the number of doctors employed by Pacific Ministries of Health between 2012 and 2019. Qualitatively, there have been some notable improvements in the medical workforce and health delivery over this period. However, the integration of the Cuban-trained doctors into practise has been challenging, with criticisms of their clinical, procedural and communication skills, and the need for the rapid development of bridging and internship training programmes (ITPs) which were inadequately planned for at the outset of the programme. Conclusions The Cuban programme in the Pacific is an important model of development assistance for health in the region. While Cuba’s offer of scholarships was the trigger for a range of positive outcomes, the success of the programme has relied on input from a range of actors including support from other governments and institutions, and much hard work by the graduates themselves, often in the face of considerable criticism. Key impacts of the programme to date include the raw increase in the number of doctors and the development of the ITPs and career pathways for the graduates, although this has also led to the reorientation of Cuban graduates from preventative to curative health. There is considerable potential for these graduates to contribute to improved health outcomes across the region, particularly if their primary and preventative health care skills are utilised.